Advertising and Consumer Search in a Duopoly Model - Maarten C.W. Janssen; Mariëlle C. Non (Tinbergen Institute, 2005)
We consider a duopoly in a homogenous goods market where part of the consumers are ex ante uninformed about prices. Information can come through two different channels: advertising and sequential consumer search. We arrive at the following results. First, there is no monotone relationship between prices and the degree of advertising. Second, advertising and search are “substitutes” for a large range of parameters. Third, when the cost of either search or advertising vanishes, the competitive outcome arises. Finally, both expected advertised and non-advertised prices are non-monotonic in search cost. One of the implications is that firms actually may benefit from consumers having low (rather than high) search costs.
Keywords: D83; L13; M37; 330; consumer search; advertising; price dispersion; Konsumentenverhalten; Suchtheorie; Werbung; Duopol; Nash-Gleichgewicht